2011
DOI: 10.1017/s1049023x11006534
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Support Tool in Prehospital Care: A Systematic Review of Randomized Trials

Abstract: Objective: The objective of this study was to evaluate the effects of the decision support tool (DST) on the assessment of the acutely ill or injured out-of-hospital patient. Methods: This study included systematic reviews of randomized controlled trials (RCT) where the DST was compared to usual care in and out of the hospital setting. The databases scanned include: (1) Cochrane Reviews (up to January 2010); (2) Cochrane Controlled Clinical Trials (1979 to January 2010); (3) Cinahl (1986 to January 2010); and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(114 reference statements)
0
17
1
Order By: Relevance
“…In the intervention group, there was an insignificantly (3 minute) longer assignment time for individuals who were sent to a CH than for those sent to the ED. These findings are different from those of earlier studies, which found that using a decision support tool in the prehospital context increased EMS assignment time but in the long run decreased the time until arrival at the final healthcare alternative.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the intervention group, there was an insignificantly (3 minute) longer assignment time for individuals who were sent to a CH than for those sent to the ED. These findings are different from those of earlier studies, which found that using a decision support tool in the prehospital context increased EMS assignment time but in the long run decreased the time until arrival at the final healthcare alternative.…”
Section: Discussioncontrasting
confidence: 99%
“…How to direct older adults is an advanced assessment process, and the system and tool were developed to secure the individual's safety and to guide the ambulance nurses in making correct decisions. There are studies that argue that a decision support tool improves EMS personnel's clinical assessment skills and that a decision support tool is required to help ambulance personnel identify individuals who would benefit from bypassing the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows some studies about the application of decision support systems in prehospital emergency care. 22,[32][33][34][35][36][37][38][39][40][41][42][43][44]…”
Section: Kovalchuk Et Al (2018) 41mentioning
confidence: 99%
“…Four features have been identified as important factors for the ability of decision support systems to improve clinical practice; the decision support is computer based, gives support as part of natural workflow, the decision support is delivered at the time and location of the decision making and actionable recommendations are provided [18]. There is limited evidence relating to the effect of CDSS in a prehospital setting [19]. In a recent simulation study of a CDSS effect of compliance to guidelines and CDSS effect of on-scene time (OST), improved guideline compliance was found among the ambulance clinicians who used a CDSS in two simulated patient cases compared with those that used guidelines in the usual paper format, but the group using the CDSS also spend more time on-scene [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited evidence relating to the effect of CDSS in a prehospital setting [19]. In a recent simulation study of a CDSS effect of compliance to guidelines and CDSS effect of on-scene time (OST), improved guideline compliance was found among the ambulance clinicians who used a CDSS in two simulated patient cases compared with those that used guidelines in the usual paper format, but the group using the CDSS also spend more time on-scene [19]. …”
Section: Introductionmentioning
confidence: 99%